THE ANALAYSIS OF ELLIPSIS IN THE CHRONICLES OF NARNIA FILM BY CLIVE STAPLES LEWIS - Mrs. Herlina (Channing : Journal of English Language Education and Literature, 2016)
Since the ellipsis as a notion is probably a universal, it should appear in all types feature of language includes in ellipsis elements used. Based on the problems, the researcher wants to investigate what are the ellipsis elements used and how are the ellipsis expressed in The Chronicles of Narnia Film By Clive Staples Lewis?. In order that, they give significance theoretically to analyze, find out, and describe the ellipsis elements used and expressed in The Chronicles of Narnia film, and practically it gives contribution for teachers, students, researcher, and other researchers. The technique used to collect the data was documentation, such as observed by watching The Chronicles of Narnia film. The data was taken from the conversation of dialogue transcript. From the data that have been analyzed, it was found that there were three types of ellipsis elements that occurred in analysis of ellipsis in The Chronicles of Narnia film. The most frequent types were verbal ellipsis occurred 22 times (55%), clausal ellipsis occurred 17 times (42.5%), and nominal ellipsis occurred only once (2.5%). Verbal ellipsis was the most productive types. It occurred more than 50 % of all the types the analysis of ellipsis in The Chronicle of Narnia film.